Multiparametric MRI and MRI/TRUS fusion guided biopsy for the diagnosis of prostate cancer - Schütz, Viktoria; Kesch, Claudia; Dieffenbacher, Svenja; Bonekamp, David; Hadaschik, Boris; Hohenfellner, Markus; Radtke, Jan Philipp (Molecular & diagnostic imaging in prostate cancer, 2018)
Purpose of this chapter To demonstrate the timing, benefits, limitations and current controversies of multiparametric magnet resonance imaging (mpMRI) combined with fusion guided biopsy and consider how additional incorporation of multivariable risk stratification might further improve prostate cancer (PC) diagnosis.Recent findings MpMRI has been shown to add important information to the diagnostic pathway for prostate cancer. Fusion biopsy has also shown advantages in comparison to standard practice for biopsy-naïve men and men with previous biopsy in large prospective studies providing level 1b evidence. Adding upfront multivariable risk stratification followed by or combined with mpMRI diagnostic accuracy can further be improved. Regarding active surveillance (AS), mpMRI in combination with fusion biopsy can support initial candidate selection and may help to monitor disease progression. However, mpMRI and fusion biopsy are not without failure and conflicting data exists to what extend (systematic) biopsies can be omitted.Summary The integration of mpMRI into the diagnostic pathway for PC can add important information for further decision making, yet more prospective and randomized data is needed to establish reliable procedure standards after mpMRI acquisition.